Globalization and The Crisis in Islamic Education: Al-Attas’ Epistemological Response and The Reconstruction of Adab-Based Pedagogy - Saeful Anwar; Hoerul Umam (JURNAL YAQZHAN: Analisis Filsafat, Agama dan Kemanusiaan, 2025)
The rapid development of globalization has posed significant challenges to Muslim identity, particularly among the younger generation. Along with the intensification of global cultural flows, the erosion of Islamic moral values has become increasingly apparent. This study explores the educational reconstruction efforts needed to preserve Islamic civilisation by analyzing the educational philosophy of Syed Muhammad Naquib Al-Attas. This research employs a qualitative library approach by analyzing Al-Attas’s major works and relevant secondary literature. Data analysis includes thematic categorization, interpretative reading, and structured descriptive synthesis of Al-Attas’s epistemological and pedagogical frameworks. Findings indicate that Al-Attas’s philosophy of education emphasizes the purification of knowledge through Westernization and the restoration of adab (ethical discipline) as the foundation of education. He criticizes Western epistemology as secular, dualistic, and skeptical, and proposes a tawhid (unitive) epistemology rooted in Islamic metaphysics. Al-Attas’ model integrates the disciplines of fardhu’ ain and fardhu kifayah, and suggests methods based on tawhid and metaphorical reasoning. This offers a transformative educational paradigm relevant to global society. Al-Attas’s adab-centred concept of education provides a comprehensive alternative to Islamic educational reform, harmonizing knowledge, ethics, and spiritual goals in addressing contemporary moral crises.